FORMATION OF PATRIOTIC IDEAS AMONG YOUTH THROUGH THE IDEOLOGY OF INTELLECTUALS IN NEW UZBEKISTAN - Sodiqov Abduhalil Abduqaxxor o'g'li (International Scientific and Current Research Conferences, 2025)
This article theoretically and practically examines the influence of intellectual ideology on the formation of youth patriotism in the conditions of New Uzbekistan. The study analyzes the role of intellectual activity in developing patriotic feelings through the awareness of national identity, introduction of historical and cultural heritage and values into the consciousness of youth. The article explores the importance of intellectual ideology in promoting the national idea, strengthening the spiritual immunity of youth, and developing modern thinking. The responsibility and potential of intellectuals for strengthening youth patriotism under modern globalization conditions are illuminated based on empirical data. The research results define the mechanisms of influence of intellectual ideology on enhancing youth patriotism and prospective directions of development.